Students' Perception on Self-Directed Learning (SDL) in Learning English by Using Youtube Video - Novita Kusumaning Tyas (Institut Agama Islam Negeri Palopo, 2022)
The dependency of the teachers' role in the teaching learning process carried out by the students is one of the crucial problems in Indonesia. On the other hand, in this digital age, independence is needed for students. Students who only depend on the teacher in the class will be left behind and make slower progress in their learning achievement. Classroom time is limited, so learners are encouraged to take responsibility for their own learning and to learn independently beyond the classroom. This is called self-directed learning (SDL). This study aims at describing the students’ perception on Self- Directed Learning (SDL) in learning English by using Youtube Video. The method used in this study is descriptive qualitative research. The participant of this study is third- semester students of the Informatics Management Program in Stekom University Semarang. The data were collected by using a questionnaire. The findings showed that most of the students enjoy in implementation of SDL in learning English but they still need tutor in their learning process.